Staging Afropolitans' Selfhood in Chimamanda Ngozi Adichie’s Americanah (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
Among many emerging Afropolitan authors who write about and for Africa through sharing their own life experiences out of and in Africa is the distinctive novelist Chimamanda Ngozi Adichie, who re-opens the debate around African immigrant identities in her award-winning novel "Americanah" (2013). Thus, the aim of this study is to trace the many components that lead to identity formation and the ways in which the Afropolitans fashion their selfhood as presented in Adichie's "Americanah." In this novel, Adichie challenges the Whites and forces dramatic debates on selfhood as well as on discomforting and unpalatable issues of racism and colonialism. Therefore, and based on postcolonial theory and Afropolitanism, the study displays a multifaceted vision of the protagonists’ experience by going full circle and by returning to their home country, as well as their transformation through such experience.The main theme of the book is the selfhood of Afropolitans, as embodied by two immigrants, Ifemelu and Obinze, who flee Nigeria in search of a better life in the West, the United States, and Great Britain. But racial prejudice in Western countries makes them feel like "others," which makes them feel like they don't belong and affects their decision to go back. This investigation shows how the characters' struggles are caused by complex kinds of gender, race, and class repression that are recurrent throughout the diaspora and manifest as racism, stereotyping, identity alteration, etc. Ifemelu, the protagonist of the main novel, writes an anonymous blog that offers cultural commentary on racial relations in America from the perspective of an African immigrant. Ifemelu boldly expresses her support for African Americans via her blog, but she also reveals how common white Americans believe that all Afropolitans—regardless of their country of birth—share a common identity of cultural oppression.Lastly, the study highlights the various aspects of Afropolitans' lives that are influenced by their skin tone or place of birth. The results show that the identities of the heroes are portrayed as intricate, multifaceted identities created by crossing international borders. The study also finds that there are similarities in the experiences of Nigerian immigrants with racism, stereotyping, and identity transition. The halfhearted affair shows that Ifemelu and Obinze get demoted while trying to find work in America. In Nigeria, the occupations they can afford are either small-scale or low-status positions that fall below their qualifications. Despite having higher degrees, they work as taxi drivers with master's degrees, toilet cleaners with bachelor's degrees in Obinze's case, or waiters or nannies in Ifemelu's case. Migration, irrespective of their standing in Nigeria prior to their emigration, treats Nigerian immigrants as second-class citizens.